Empowering Rawabadak: A Digital Marketing Initiative for Local Business Growth - Nelloh, Liza; Ramadhan , Alvaro Putra; Fadillah , Ivan; Immanuel , Timothy (Journal of Sustainable Community Development (JSCD), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in supporting local economic development; however, many face persistent challenges related to limited managerial capacity and inadequate utilization of digital marketing tools. This article examines a Community Involvement Project (CIP) conducted in Rawabadak, Indonesia, aimed at empowering local MSMEs through structured digital marketing interventions. The program involved business and digital marketing mentoring, the development of tailored social media content, and the promotion of a community-based marketplace known as the CIP Bazaar. A descriptive qualitative approach was employed, with data collected through direct observation, mentoring documentation, digital campaign records, and feedback from participating business owners. The findings indicate that the program contributed to increased digital visibility and engagement of MSMEs, improved understanding of basic marketing concepts among business owners, and enhanced community participation during the bazaar event. The results demonstrate that targeted digital marketing assistance combined with community engagement can strengthen MSME competitiveness and support sustainable local economic development. This study highlights the potential of community-based digital empowerment programs as an effective model for MSME development in urban communities.